Gambaran MCH, MCV dan MCHC Pada Ibu Hamil Trimester II di Puskesmas Wonokerto I Kabupaten Pekalongan - Subur Wibowo; Anisah Fauziyah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Anemia is a dangerous condition that can occur in pregnant women, this case often occurs in the first, second and third trimesters. Anemia is a reduction or reduction in the capacity of the blood to carry oxygen. Based on data from the Indonesian Ministry of Health (Kemenkes), the population of pregnant women who experience anemia is 37.1%. The proportion of anemia in pregnant women in urban areas is 36.4% and in rural areas is 37.8%. The most common type of anemia in pregnant women is microcytic hypochromic anemia (59% of pregnant women are anemic). This study aims to determine the description of MCH, MCV and MCHC in pregnant women in the second trimester at the Wonokerto I Community Health Center, Pekalongan Regency. The research method used is descriptive. The research was conducted at the Wonokerto I Community Health Center Laboratory, Pekalongan Regency. The total sample was 20 second trimester pregnant women. Using the Hematology Analyzer Dirui BCC 3600. From 20 samples of pregnant women in the second trimester, the MCV was obtained for 11 Normocytic pregnant women (80-100 fL), 8 Microcytic pregnant women (<80 fL), and 1 Macrocytic pregnant woman (>100 fL). . MCH description of 9 Normochrome pregnant women (27-34 pg), 10 Hypochrome pregnant women (<27 pg) and 1 Hyperchrome pregnant mother (>34 pg). MCHC description of 9 pregnant women is Normal (32-36 g/dL), 10 pregnant women are Low (<32 g/dL) and 1 pregnant woman is High (>36 g/dL). The conclusion of this study is that from 20 samples of second trimester pregnant women, the most common type of anemia was Hypochromic Normocytic Anemia with low and normal MCHC index levels.